Using ultrasound measurements of rump fat to assess nutritional condition of woodland caribou in northern British Columbia, Canada - Gustine, David D.; Parker, Katherine L.; Heard, Douglas C. (Rangifer, 2007)
Body reserves (fat and protein) of cervids are important to the reproductive success of individuals, and therefore may limit productivity of populations. We used a portable ultrasound machine to measure thickness of rump fat for 39 woodland caribou (Rangifer tarandus caribou) captured in the winters (January–February) of 2003 and 2004. We compared thickness of rump fat between pregnant and non-pregnant individuals in the Besa-Prophet drainage of northern British Columbia, Canada. Thirty-eight of the 39 females captured in British Columbia were adults and 34 of the adult caribou were pregnant (89.5 ± 5.1%, x– ± binomial SE). Pregnant individuals had more rump fat (0.60 ± 0.067 cm) than nonpregnant animals (0.20 ± 0.029 cm). Recognizing that deposition and mobilization of fat vary with age and possibly across the winter season, ultrasonography can be used as a non-invasive technique in the field to assist in estimating body fat of caribou.